(untitled) (Scientia Agropecuaria, 2023)
The tree composition in cocoa agroforestry systems (CAFS) in Guatemala is valued for providing a number of ecosystem services. Despite the importance of the trees in these systems, little is known about the tree species richness and its contribution to the conservation of diversity. We studied the botanical composition of CAFS of different ages in the Alta Verapaz department of Guatemala. In total, 70 survey plots with a size of 2500 m2 were established. An inventory was carried out in each sampling unit, recording the tree species present and measuring the diameter at breast height (DBH 1.30 m) and the height of each tree. The Importance Value Index (IVI) was calculated and species richness and the similarity between sites were evaluated. A total of 2519 trees, belonging to 59 species and 34 families were identified. The species with the highest IVI was Gliricidia sepium (Jacq.) Kunth. The CAFSs with the highest and lowest species richness were those of 9-12 and 27 years old, respectively (H´=1.99, H´=0.34). This behavior can be explained by the fact that growers work to enrich the agroforestry systems with a broad diversity of species in the first years which they then begin to harvest at around 16 years of age. A discriminant analysis of principal components (DAPC) and the Jaccard Similarity Index were used to show that several AFS were similar in terms of composition and botanical diversity. Given the tree diversity within the CAFS, these can be acknowledged as areas with good potential for the conservation of overall biodiversity. We recommend education programs for local growers about the benefits of shade management during the production cycle of cocoa to preserve the botanical composition and structural complexity of the AFS.